Different mechanical responses of dimorphic forms of anthracene schiffbase crystal - Lakshmipathi, Madhumathi; Tothadi, Srinu; Emmerling, Franziska; Bhattacharya, Biswajit; Ghosh, Soumyajit (Journal of Molecular Structure, 2022)
We obtained concomitant dimorphic forms of Anthracene Schiffbase (N-(anthracen-9-yl methylene)-2,5dichloroaniline) from hexane solvent. Two polymorphs can be differentiated by their morphology and mechanical properties. One form is long acicular type and elastically bendable while another form is block shaped and brittle in nature. Mechanical property is attributed to underlying crystal packing. Hirshfeld analysis and energy framework calculations were done to corroborate structure-property correlation of two forms (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Anthracene schiffbase; Dimorphs; Elasticity; mechanical properties